Electrochemical preparation and characterization of polypyrrole/stainless steel electrodes decorated with gold nanoparticles - Gutiérrez Pineda, Eduart Andrés (2015)
The electrosynthesis and characterization of polypyrrole(PPy)/stainless steel electrodes decorated with gold nanoparticles and the performance of the composite electrode for sensing applications is described. PPy films were grown in potassium perchlorate and sodium salicylate solutions under comparable electropolymerization conditions. Polymer films prepared in the presence of perchlorate ions exhibited wormlike structures, whereas columnar structures were obtained in salicylate-containing solutions. Voltammetric response of PPy films prepared in salicylate solutions was more reversible. PPy films were decorated with gold nanoparticles obtained by a double step potentiostatic electrodeposition routine that allowed fine control of deposit characteristics. Analysis of deposits was performed by means of SEM and confocal Raman spectroscopy. The electrocatalytic activity of the Au/PPy electrodes was assessed for the electro-oxidation of hydrazine and hydroxylamine. Results showed a successful optimization of the route of synthesis that rendered nanocomposite electrode materials with promising applications in electrochemical sensing.